(untitled) (Orfeu, 2022)
The many transformations, as psychology, physical and social, that appears in adolescence can make the individuals start doubting about their abilities and not seeing the possibility of musical development through the practice. Thus, the musical instrument teacher has a relevant role in maintaining these students’ motivation, in particular. The general objective of this study was, therefore, meet the instrument teachers’ beliefs, opinions and attitudes about Basic Psychological Needs (DECI; RYAN, 2000), in the context of promoting adolescents students’ motivation to learn music. To reach this objective the used methodology was survey study and the data was collected through a questionnaire. The obtained results bring considerations for music teachers when it comes to planning and driving classes, that can, therefore, enlarge adolescent’s motivation. It is proven, through the results, that a good regulation of motivation is able to allow more effective learning and performance.